Dexamethasone Cyclophosphamide Pulse Therapy in Immunobullous Diseases: Our Experience - Parajuli, S; Paudel, U (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Dexamethasone cyclophosphamide (DC) pulse therapy seems to be emerging affordable modality of treatment in immunobullous disorders. The objective of this study was to describe the effectiveness of DC pulse therapy in immunobullous disease in our setting. Methods: This was a retrospective study carried out in the Department of Dermatology of a tertiary referral centre by reviewing the medical records of all the patients of immunobullous diseases receiving DC pulse therapy from January 2010 through January 2014. Results: There were a total of 10 patients of immunobullous disease receiving the therapy during above mentioned period (7- Pemphigus Vulgaris, 2- Pemhigus foliaceus, 1- Bullous Pemphigoid).There were 5 males and 5 females receiving the therapy, with the mean age of the diseased at presentation being 47.4 years. Out of 10 patients, 2 patients were lost to follow up after the 1st pulse. Out of 8 patients, 6 patients (75%) achieved clinical remission. The mean time to remission was 10.6months (Range: 3 months to 23 months). The major adverse effects seen during therapy were diabetes (50%) and leucopenia (20%). Conclusions: DC pulse therapy seems to be effective treatment modality in the management ofimmunobullous disorder in our setting with good safety profile.